Going to Scale: Experiences Implementing a School-Based Trauma Intervention - Nadeem, Erum (School Psych Rev, 2011)
This article describes implementation experiences “scaling up” the Cognitive Behavioral Intervention for Trauma in Schools (CBITS)—an intervention developed using a community partnered research framework. Case studies from two sites that have successfully implemented CBITS are used to examine macro- and school-level implementation processes and strategies used to address implementation issues and create a successful implementation support system. Key elements of the implementation support system include pre-implementation work, ongoing clinical and logistical implementation supports, promotion of fidelity to the intervention’s core components, tailored implementation to fit the service context, and a value on monitoring child outcomes.